Anti-Inflammatory Effect of a TCM Formula Li-Ru-Kang in Rats With Hyperplasia of Mammary Gland and the Underlying Biological Mechanisms - Wang, Yingying; Wei, Shizhang; Gao, Tian; Yang, Yuxue; Lu, Xiaohua; Zhou, Xuelin; Li, Haotian; Wang, Tao; Qian, Liqi; Zhao, Yanling; Zou, Wenjun (Frontiers in Pharmacology, 2018)
Li-Ru-Kang (LRK), a formula of eight traditional Chinese medicines (TCM), has been used to treat hyperplasia of mammary gland (HMG) in TCM clinics. However, how LRK works in HMG patients is unclear. To explore the possible mechanisms of LRK against HMG, the network pharmacology was used to screen the potential targets and possible pathways that involved in LRK treated HMG. Rat HMG model induced by estrogen and progesterone was used to further verify the effects of the key molecules of LRK selected from the enriched pathways on HMG. Nipple heights and diameters were measured and uterus index was calculated. The histopathological changes of mammary gland tissue were detected by hematoxylin-eosin (H&E) staining. Western blot was used to detect the phosphorylation of ERK, JNK and P38. And immunohistochemistry staining was performed to evaluate the levels of estrogen receptor α (ERα), progesterone receptor (PR), nuclear factor-(NF-)κB (p65), interleukin-1β (IL-1β), tumor necrosis factor α (TNF-α), cyclooxygenases 2 (COX-2), inducible nitric oxide synthase (iNOS), 8-hydroxy-2’deoxyguanosine (8-OHdG) and nitrotyrosine (NT). Our results indicate that LRK treatment rescues significantly nipples height and diameter, decreases uterus index and ameliorates hyperplasia of mammary gland. LRK treatment also markedly attenuates the over-expression of IL-1β, TNF-α, COX-2 and iNOS, and suppressed the formation of 8-OHdG and NT. Furthermore, LRK treatment significantly inhibits the phosphorylation of JNK, ERK and p38 and expression of NF-κB (p65), interestingly, LRK treatment has no effect on the expression of ERα and PR. Our data suggest that the LRK treatment protects the mammary glands from the damage of oxidative stress and inflammation induced by estrogen and progesterone, via suppresses of MAPK/NF-κB signaling pathways without affecting on the expression of ERα and PR.